2009
DOI: 10.1002/jmv.21495
|View full text |Cite
|
Sign up to set email alerts
|

293 cells over‐expressing human ADI1 and CD81 are permissive for serum‐derived hepatitis C virus infection

Abstract: Human aci-reductone dioxygenase 1 (ADI1) is a member of the Cupin superfamily. It binds to and inhibits the activities of membrane-type 1 matrix metalloproteinase, a protein known to interact with the tight junction protein, claudin-1. Previously, a variant protein, named submergence-induced protein-like factor (Sip-L), consisting of ADI1 amino acids 64-179, was found to support hepatitis C virus (HCV) infection and replication in 293 cells. In the present study, it was discovered that over-expression of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 37 publications
(50 reference statements)
1
20
0
Order By: Relevance
“…(iv) Protein folding. Several cochaperone proteins of the DNAJ protein family, which regulate the heat shock proteins HSP70 and HSP90 involved in HCV replication via NS3 viral protein (39), were upregulated, of which DNAJB1 is necessary for HCV replication (40). Several members of the immunophilin protein family, cis-trans prolyl isomerases that accelerate protein folding, were downregulated (FKBP5, FKBP7, FKBP3, FKBP9, FKBP1B, and FKBP1A), while cyclophilin B, which stimulates the function of the HCV RNA polymerase NS5B (41), was upregulated.…”
Section: Main Biological Processes Regulated By Hcv At the Translatiomentioning
confidence: 99%
“…(iv) Protein folding. Several cochaperone proteins of the DNAJ protein family, which regulate the heat shock proteins HSP70 and HSP90 involved in HCV replication via NS3 viral protein (39), were upregulated, of which DNAJB1 is necessary for HCV replication (40). Several members of the immunophilin protein family, cis-trans prolyl isomerases that accelerate protein folding, were downregulated (FKBP5, FKBP7, FKBP3, FKBP9, FKBP1B, and FKBP1A), while cyclophilin B, which stimulates the function of the HCV RNA polymerase NS5B (41), was upregulated.…”
Section: Main Biological Processes Regulated By Hcv At the Translatiomentioning
confidence: 99%
“…ADI1 is a downstream protein of ENOPH1 and has been shown to play an important role in cell apoptosis, oxidoreductase reaction and virus infection (Hirano et al, 2005; Oram et al, 2007; Cheng et al, 2009). Therefore, we speculated that ADI1 might mediate the effect of ENOPH1 on OGD-induced endothelial cell death.…”
Section: Resultsmentioning
confidence: 99%
“…ADI1 is a downstream molecule of ENOPH1 in methionine salvage pathway and has been shown to be implicated in cell apoptosis, cell growth inhibition, oxidoreductase reaction and virus infection (Hirano et al, 2005; Oram et al, 2007; Cheng et al, 2009). In addition, ADI1 is an oxidoreductase and can combine molecular oxygen donor to generate ROS (Oram et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent study, we demonstrated that human aci-reductone dioxygenase 1 (hADI1) over-expression in 293 cells enhances viral entry into cells but not replication of HCV [[20]]. ADI1, an MTA cycle enzyme, belongs to the cupin domain superfamily and has aci-reductone dioxygenase (ARD) enzymatic activity.…”
Section: Introductionmentioning
confidence: 99%